Analysis of Creativity of Thinking in Programming Learning of Mathematics Education Students of Sulawesi Barat University - Manullang, Ketrin Rinayanti; Ramadhana, Nurhikma; Yahya, Amran (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This study aims to analyze creativity in thinking in programming learning of Mathematics Education students at the University of West Sulawesi. The type of research in this study is quantitative research with a descriptive approach. The population in this study were students majoring in Mathematics Education, FKIP, University of West Sulawesi Semester III consisting of 3 class groups. The sample in this study was students majoring in Mathematics Education, FKIP, University of West Sulawesi Semester III Class A as many as 22 people. Data on student learning outcomes in programming courses were collected using performance tests and data on creativity in thinking using questionnaires. The results of the analysis of the research data obtained an average value of student programming learning outcomes of 77.5 and a value of 77.5> 70 which is the standard passing value. For creativity in thinking data, an average value of 83.36 was obtained and an average percentage of creativity in thinking was 79.39% and this value is included in the high category. There are 22 samples (100%) that have creativity in thinking in the high category. Of the 22 samples that have high thinking creativity, there are 3 samples (14%) with high thinking creativity that have learning outcome values ​​<70 and there are 19 samples (86%) with high thinking creativity that have learning outcome values ​​≥70. Based on the results of data analysis, it can be concluded that samples that have high thinking creativity also have high programming learning outcomes.